Impact of climate conditions on the performance of adaptive air handling unit - Madhwesh N; Sampath Suranjan Salins; Shiva Kumar (International Journal of Thermofluids)
Thermal comfort inside the Building space, houses, and offices are controlled by using the heating, ventilation, and air conditioning (HVAC) systems. To reduce energy consumption and achieve optimal performance, building automation plays a crucial role. This work focuses on a detailed analysis of the air handling unit, which is used to maintain thermal comfort within a room in a Dubai Climatic conditions. An air handling unit was constructed for the study, and experiments were conducted under various climatic conditions to assess the performance of the humidifier and dehumidifier and their impact on thermal comfort within the room. The results showed that the system achieved a maximum dehumidification efficiency of 96.06 %, a moisture removal rate of 2.25 g/s, an evaporation rate of 0.16 g/s, and a coefficient of performance of 0.8. The thermal comfort parameters, including Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD), remain within acceptable limits for inlet temperatures of 25 °C and 40 °C across all inlet relative humidity values. However, temperatures outside these ranges did not fall within the thermal comfort limits. It was found that energy and cost savings per hour amounted to 22.85 %.